FINANCIAL RATIOS OF THE COUNTRY’S ENTERPRISES IN THE FACE OF ECONOMIC GROWTH AND DECLINE - Misiūnas, Algimantas (Ekonomika, 2010)
The author analyses financial ratios of Lithuanian enterprises by economic sectors in the period from 1998 to 2008. During the period in question, which was selected consciously and purposefully, Lithuanian economy experienced two recessions: the first one took place after the Russian crisis 1998 and the second started in 2008, together with the global financial crisis. In the period between the two crises, a rapid economic development was observed.In the paper, the efficiency of the sectors of Lithuanian economy is assessed using various financial ratios, reflecting various aspects of performance of an economic entity: its capability to secure income, to perform profitably, to properly manage liabilities, to make proper use of available potential, to avoid jeopardising its further performance. Since no common methodology for the assessment of economic efficiency has been developed, it is offered to form an integral aggregate ratio to make possible the intercomparison of economic sectors and to determine the level of efficiency based on a set of financial ratios but not on each of them separately. The experiments and calculations performed showed that most suitable is the weighted arithmetic mean method.